Development of a multi-channel readout ASIC for a fast neutron spectrometer based on GEM-TPC - 何力 邓智 刘以农 李玉兰 (Chinese physics C, 2014)
A multi-channel front-end ASIC has been developed for a fast neutron spectrometer based on Gas Electron Multiplier （GEM）-Time Projection Chamber （TPC）. Charge Amplifier and Shaping Amplifier for GEM （CASAGEM） integrates 16＋1 channels： 16 channels for anodes and 1 channel for cathode. The gain and the shaping time are adjustable from 2 to 40 mV/fC and from 20 to 80 ns, respectively. The prototype ASIC is fabricated in 0.35 μm CMOS process. An evaluation Print Circuit Board （PCB） was also developed for chip tests. In total 20 chips have been tested. The integrated nonlinearity is less than 1%. The equivalent noise electrons is less than 2000e when the input capacitor is 50 pF. The time jitter is less than 1 ns. The design and the test results are presented in the paper.